Journey space in the " Ra’e" Ajaj From stimulating the subject to textual significance - يعقوب, عبد الكريم; محمود , راما (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims to study the story in the poem of Ajaj, as a theme that shows the realm and spaces (desert, animal and sea), which are spaces capable of achieving perceptions and indications. The journey interacted with the other elements of the Rajaz poem in an integrated structure based on transformation and continuity, contrary to stability and residing, and a receptor for subjects and functions, and a detector of indications and meanings. But the completion of the techniques of the story as dialogue and characters and time and place and events and the node and the solution, does not reach the degree of narrative with its completion of elements and techniques. In the space of the journey of Ajaj, we read the presence of creation and objects, as a new creation has its vital existence in the poetic text in a narrative field whose structure and reference is based on the establishment of images and their construction in the aesthetic composition of the poetic effect that we seek to construct the textual significance.